Heresy or Hermeneutics - Charles Hirschkind (International Institute of Islamic Thought, 1995)
Islam/Islamism The debate I shall discuss here arose following Cairo University's decision to refuse tenure to a professor of Arabic language and literature, Nasr Hamid Abu Zayd, in light of an unfavorable report by the tenure committee entrusted to review his scholarly work. Supporters of Abu Zayd quickly brought the case to national attention via the Egyptian press, thereby precipitating a storm of often shrill writing from all sides of the political spectrum, in both the journalistic and academic media. Subsequently, as an Islamist lawyer tried to have Abu Zayd forcibly divorced from his wife on the grounds that his writings revealed him to be an apostate, the foreign media also picked up the story and transformed the case into an international event. In what follows, I will focus on one comer of this debate concerning contrastive notions of reason and history, issues which, I wish to argue, are implicated deeply in the forms of political contestation and mobilization occurring in Islamic countries today. Such topics seldom appear in discussions that take Islamic movements or Islamic revival as their object, an omission perhaps attributable to the conceptual frames informing these discussions. As we may note, the idea of a social movement presupposes a self-constituting subject, independent from both state and tradition: a uni- linear progressive teleology; and a pragmatics of proximate goals, namely, the spatiotemporal plane of universal reason and progressive history, the temtory of modem humanity. Such an actor must fulfill the Kantian demand that reason be exercised autonomously and embodied in a sovereign subject. In contrast, one may argue that the protagonist of a tradition of inquiry founded on a divine text is necessarily a collective subject, one that seeks to preserve and enhance its own exemplary past. As such, Islam never satisfies these modem demands and thus must always remain somewhat outside the movement of history as a lesser form of reasoning. Indeed, the assumption of a fundamental opposition between reason and religion, an assumption that is central to the historical development of both modem concepts during the sixteenth and seventeenth centuries, has meant that investigations into the rationalities of religious traditions have rarely been viewed as essential to the description or explanation of those religions.’ Consequently, to pose a question in regard to Islam generally means that one must either be asking about politics (the not-really-Islam of “Islamism,” or “political Islam”) or about belief, symbols, ritual, and so on, but not about styles of reasoning. We find, for example, that within political economy discussions of oppositional movements in the Middle East, Islam is viewed generally as little more than the culturally preferred idiom through which opposition, be it class or otherwise, may be expressed.* Unquestionably, the best of these studies have told us much about the kinds of material conditions and the specific intersections of capital and power that have enabled, or undermined, arguments, movements, forms of practice, including, among others, Islamic ones.’ Founded upon the same set of Enlightenment assumptions mentioned above, these writings have provided conflicting accounts of the kinds of modem forces transforming the contemporary political structures of the Middle East but are ill-equipped when it comes to analyzing those dimensions of social and political life rooted in nonwestern traditions ...